Acceleration at z > 1? - Amendola, Luca (Monthly notices of the Royal Astronomical Society, 2003)
Most models of dark energy predict the beginning of the accelerated epoch at z≤ 1. However, there is no observational or theoretical evidence in favour of such a recent start of the cosmic acceleration. In fact, a model of dark energy coupled to dark matter is explicitly constructed which (a) is accelerated even at high z, (b) allows structure formation during acceleration, and (c) is consistent with the Type Ia supernovae Hubble diagram, including the farthest known supernova SN1997ff at z≈ 1.7. It is shown that the accelerated epoch in this model could have started as early as z≈ 5.
Gesehen am 17.11.2017